microRNAs profiling of small extracellular vesicles from midbrain tissue of Parkinson’s disease - Li, Zhengzhe; Chen, Dongdong; Pan, Renjie; Zhong, Yanbiao; Zhong, Tianyu; Jiao, Zhigang (Frontiers in Molecular Neuroscience, 2023)
Small extracellular vesicles (sEVs) are generated by all types of cells during physiological or pathological conditions. Growing attention has focused on tissue-derived small extracellular vesicles (tdsEVs) because of isolating from a single tissue source. Understanding the expression profile of microRNA (miRNA) in sEVs derived from the substantia nigra of midbrain tissues (bdsEVs) and their roles is imperative for understanding the pathological mechanism, improving the diagnosis and treatment of Parkinson's disease (PD). bdsEVs from a rat model of PD and sham group were separated and purified in combination using ultracentrifugation, size-exclusion chromatography (SEC), and ultrafiltration. Then, miRNA profiling of bdsEVs in both groups were evaluated using next-generation sequencing (NGS). Between the two groups, the expressed levels of 180 miRNAs were significant differences, which were 114 up-regulated and 66 -down-regulated in bdsEVs of PD rats compared with those of the sham group (p value < 0.05). The targets of differential expression miRNAs were predicted by miRanda and RNAhybrid, and involved in the signaling pathways and cellular function have been analyzed through the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway and Gene Ontology (GO). Furthermore, we explored and compared the expressed levels of miR-103-3p, miR-107-3p, miR-219a-2-3p, and miR-379-5p in bdsEVs, sEVs derived from plasma and plasma of both group rats. Interestingly, the expressed levels of miR-103-3p, miR-107-3p, miR-219a-2-3p, and miR-379-5p were elevated in bdsEVs and sEVs from plasma; in contrary to this, their expressed levels were decreased in the plasma of rat model of PD. In summary, all data indicated that miRNAs may play an important role in the onset and development of PD, and miRNAs need to be selected carefully as a researched subject for exploring the pathological mechanism, the potential values of diagnostic markers and therapeutic targets of PD.